1993
DOI: 10.1002/bjs.1800800431
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liver blood flow associated with the growth of hepatic LV10 and MC28 sarcomas in rats

Abstract: Abnormalities in liver blood flow are known to occur in patients and animals with overt hepatic tumour. This study investigated the changes in liver blood flow associated with the development of overt hepatic tumour in two different models. Hepatic tumour was induced by intraportal inoculation of either 300 LV10 sarcoma cells or 10(5) MC28 sarcoma cells in rats. Liver blood flow and hepatic haemodynamics were measured 3 weeks later when overt liver tumour was present. The hepatic perfusion index (HPI), the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…An increase in the hepatic perfusion index has been demonstrated in number of experimental liver tumour models, and this has been shown to be due to a reduction in portal venous inflow associated with increased gastrointestinal vascular resistance (Nott et al, 1989;Hemingway et al, 1991;1993). The results of the present experiment suggest that, in the HSN sarcoma model, this is at least partly mediated by a circulating agent.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…An increase in the hepatic perfusion index has been demonstrated in number of experimental liver tumour models, and this has been shown to be due to a reduction in portal venous inflow associated with increased gastrointestinal vascular resistance (Nott et al, 1989;Hemingway et al, 1991;1993). The results of the present experiment suggest that, in the HSN sarcoma model, this is at least partly mediated by a circulating agent.…”
Section: Discussionsupporting
confidence: 58%
“…Quantitative flowmetry has confirmed that hepatic arterial flow is increased, but has shown that a substantial reduction in portal venous blood flow also contributes to the elevation of the perfusion index (Leen et al, 1991). Experiments in rat liver tumour models have demonstrated a similar rise in the HPI that is due entirely to reduced portal venous inflow secondary to increased splanchnic vascular resistance (Nott et al, 1989;Hemingway et al, 1991;1993). This suggests that the means by which the tumour influences hepatic haemodynamics may not be purely local in nature.…”
mentioning
confidence: 99%
“…In the literature four different routes have been reported as potential ways to induce, experimentally, liver neoplastic disease: tumour implantation in the liver [9,23,29,30,31,33]; neoplastic cell infusion through the portal route [10,11,12,13,14,34]; liver metastasis development after intracaecal implantation of tumour [35,36]; and chemical liver tumour induction [37].…”
Section: Discussionmentioning
confidence: 99%
“…The association between liver metastases and altered liver blood flow has been primarily demonstrated by dynamic scintigraphy both in animal experiments [9,14] and in clinical series [8,15,16,17].…”
Section: Introductionmentioning
confidence: 99%